Dehydration/polycondensation of lactic acid under microwave irradiation - Guba, G.Ya.; Gusar, A.O.; Bakibayev, A.A.; Tazhbayev, Ye.M.; Minayeva, Ye.V. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
In this paper the effect of microwave irradiation power (MW) on the processes of polycondensation of lactic disturbed total internal reflection acid (LA) was studied for the first time. LA polycondensation was carried out in a multimodal reactor in a vacuum while bubbling with nitrogen at powers of 80, 130, 280, 360 and 500 watts. The change in the temperature of the LA sample under conditions of MW as a function of time and irradiation power was determined. Based on the data of 1H NMR and IR spectroscopy, it was suggested that at 80 W the molecules of physically bound water are mainly removed. The formation of lactic acid oligomers (LAO) occurs at a power of 130–280 W along with the removal of water and LA. Complete removal of water from LAO occurs at 360 watts. When LA is heated at MW power of 430 W, the formation and isolation of colorless crystals is observed, which can be classified by the IR spectra as lactide molecules (νC=O is 1770 cm–1, νC–O–C is 1240 cm–1). The molecular weight of LAO decreases at a power of 430 W and above. The kinetic curves of LA polycondensation at 130, 280 and 360 W are presented. The process of LA polycondensation at 360 watts is optimal. It was established that the rate of LA dehydration under MW conditions increases by 15–20 times as compared with carrying out the process under normal heating conditions.
Сүт қышқылының микротолқынды сəулелендіру жағдайларында дегидратациялануы/поликонденсациялануы
Дегидратация/поликонденсация молочной кислоты в условиях микроволнового облучения
Keywords: microwave irradiation; lactic acid; polylactic acid; lactic acid oligomers; NMR spectroscopy; IR spectroscopy; specific optical rotation; molecular weight